Association of concomitant congenital diaphragmatic hernia and Hirschsprung's disease with a mutation in the FOXP1 gene: A case report - Vyacheslav Lenkov; Jason O. Robertson (Elsevier, 2024)
Introduction: Forkhead box protein P1 (FOXP1) is a transcriptional factor that plays a role in gene regulation in a wide array of human tissues. Mutations of this gene result in developmental delay, language deficits, brain, cardiac and urogenital anomalies. Some evidence also connects these mutations with congenital diaphragmatic hernia (CDH) and Hirschsprung's disease (HD). This report describes a case of a newborn with a FOXP1 mutation who was diagnosed with both CDH and HD, suggesting the gene's possible association with both phenotypes. Case report: The patient was born at 38w2d to a healthy mother. Multiple congenital anomalies were discovered prenatally, including Dandy-Walker malformation, bilateral cleft lip and palate, polydactyly and syndactyly. No chromosomic aneuploidies were identified; however, whole exome sequencing analysis detected a missense mutation of FOXP1. The patient passed meconium on day-of-life zero and progressed appropriately. Presentation of CDH manifested at 7 weeks with respiratory failure following delayed intrathoracic herniation. Chest x-ray confirmed the diagnosis, and a small type A defect was identified at the time of surgery. At 12 weeks, worsening abdominal distention prompted workup of Hirschsprung's disease. Suction rectal biopsy confirmed the diagnosis. Both CDH and HD were addressed surgically upon diagnosis. Post-operative courses were uncomplicated. Conclusion: This report demonstrates an unusual association of CDH and HD in a patient with a FOXP1 mutation. Both diseases were on the mild spectrum and demonstrated delayed presentations. The role of this FOXP1 mutation as a genetic cause of both diseases warrants further investigation.